2020
DOI: 10.1111/mmi.14503
|View full text |Cite
|
Sign up to set email alerts
|

Specificity profile of NAT/NCS2 purine transporters inSinorhizobium(Ensifer)meliloti

Abstract: Soil bacteria that can form nitrogen-fixing symbiotic nodules on legumes, collectively called rhizobacteria or rhizobia, have a global impact on the sustainable agriculture and the cycling of nitrogen in the biosphere. In the symbiotic nodules, rhizobia are differentiated to organelle-like bacteroids, which populate the infected plant cells and specialize in reducing the atmospheric nitrogen to ammonium. The efficiency of this process depends on many factors, a central one being the proper exchange of metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
0
2
0
6
Order By: Relevance
“…In this study, in silico experiments were carried out in the catalytic site of the enzyme for estimating the validity regarding the competitive inhibition hypothesis in direct comparison with the SAR notions derived via in vitro screening and, further, for evaluating the contribution of each of the chemical functionalities present in 1 in CBS binding. For enhancing sampling accuracy, induced-fit flexible protein docking (IFD, Schrödinger LLC, New York, NY, USA, 2020) was applied on top-ranked binding geometries determined by rigid docking (Glide, Schrödinger LLC, New York, NY, USA, 2020) [ 55 , 56 , 57 , 58 ]. Overall, docking calculations showed that the dominant binding geometry of 1 would agree, yet not unambiguously, with the scenario that charge-assisted interactions are not necessary for efficient 1 binding to CBS ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, in silico experiments were carried out in the catalytic site of the enzyme for estimating the validity regarding the competitive inhibition hypothesis in direct comparison with the SAR notions derived via in vitro screening and, further, for evaluating the contribution of each of the chemical functionalities present in 1 in CBS binding. For enhancing sampling accuracy, induced-fit flexible protein docking (IFD, Schrödinger LLC, New York, NY, USA, 2020) was applied on top-ranked binding geometries determined by rigid docking (Glide, Schrödinger LLC, New York, NY, USA, 2020) [ 55 , 56 , 57 , 58 ]. Overall, docking calculations showed that the dominant binding geometry of 1 would agree, yet not unambiguously, with the scenario that charge-assisted interactions are not necessary for efficient 1 binding to CBS ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ο διαχωρισμός εξειδίκευσης που εμφανίζουν τα AzgA-like ομόλογα της E. coli διατηρείται και σε στενά συγγενικά βακτήρια όπως η Αeromonas veronii (Λάζου & Φριλίγγος, αδημοσίευτα δεδομένα), αλλά δεν εμφανίζεται σε άλλα AzgA-like ομόλογα όπως του ριζοβίου Sinorhizobium meliloti 200 , του μύκητα Α. nidulans 186 , του φυτού Arapidopsis thaliana 201 και της σπειροχαίτης B. burgdorferi 151,161 , που κωδικοποιούν μεταφορείς ευρύτερης εξειδίκευσης για την μεταφορά αδενίνης/γουανίνης/υποξανθίνης. Με βάση την εντυπωσιακά υψηλή ταυτότητα αλληλουχίας των δύο ζευγών μεταφορέων, η οποία συντηρείται και σε θέσεις σημαντικές για την λειτουργία τους, θα ήταν ενδιαφέρον να εξεταστεί η σχέση δομής-λειτουργίας αυτού του χαρακτηριστικού διαχωρισμού εξειδίκευσης.…”
Section: προκλήσεις στην μελέτη της Azga-likeunclassified
“…Οι αρχικές μελέτες για την κατανόηση των σχέσεων δομής-λειτουργίας στους AdeP και GhxP είχαν εστιασθεί στην ανάλυση του λειτουργικού ρόλου σημαντικών καταλοίπων του προβλεπόμενου κέντρου δέσμευσης πουρινών, χωρίς να έχουν αποκαλύψει θέσεις αμινοξέων που να συμβάλλουν στην διάκριση της εξειδίκευσης τους (αδενίνη ή υποξανθίνη/γουανίνη) 196 . Μελετώντας συγκριτικά τους AdeP και GhxP σε περιοχές εκτός του κέντρου δέσμευσης, αλλά και συγκρίνοντας τα προφίλ εξειδίκευσής τους με ομόλογους μεταφορείς όπως ο πρόσφατα χαρακτηρισμένος μεταφορέα ευρύτερης εξειδίκευσης Q92VC3 του S. meliloti, 200 αναμένεται να συσχετιστούν θέσεις της αλληλουχίας τους με την αναγνώριση συγκεκριμένων ομάδων πουρινικών αναλόγων.…”
Section: σκοπός της διατριβήςunclassified
“…El efecto del pH está muy relacionado con la nutrición del Ca +2 , pues existe un antagonismo entre los iones hidrógeno (H + ) y Ca +2 . En las leguminosas el nitrógeno (N) es provisto mayoritariamente desde la atmósfera a través de la simbiosis con Sinorhizobium (Ensifer) meliloti en el caso de la alfalfa (Botou, 2020) y Bradyrhizobium japonicum, en el caso de la soja (Mitran, 2018). Diferentes estudios indican que para lograr altas eficiencias en la fijación biológica de nitrógeno es necesario que el cultivo no tenga limitaciones nutricionales severas en una serie de nutrientes esenciales que participan en el crecimiento y desarrollo de estructuras radiculares y nodulares (Almeida et al, 2000;Høgh-Jensen et al, 2002;Høgh-Jensen et al, 2003;Olivera et al, 2004;Schulze et al, 2006).…”
Section: Introducción Específicaunclassified